-5-6x=4(5x+3)

Simple and best practice solution for -5-6x=4(5x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-6x=4(5x+3) equation:


Simplifying
-5 + -6x = 4(5x + 3)

Reorder the terms:
-5 + -6x = 4(3 + 5x)
-5 + -6x = (3 * 4 + 5x * 4)
-5 + -6x = (12 + 20x)

Solving
-5 + -6x = 12 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-5 + -6x + -20x = 12 + 20x + -20x

Combine like terms: -6x + -20x = -26x
-5 + -26x = 12 + 20x + -20x

Combine like terms: 20x + -20x = 0
-5 + -26x = 12 + 0
-5 + -26x = 12

Add '5' to each side of the equation.
-5 + 5 + -26x = 12 + 5

Combine like terms: -5 + 5 = 0
0 + -26x = 12 + 5
-26x = 12 + 5

Combine like terms: 12 + 5 = 17
-26x = 17

Divide each side by '-26'.
x = -0.6538461538

Simplifying
x = -0.6538461538

See similar equations:

| tw+tq=u | | 0.66=2.66b | | uw+uq=u | | 5x=2-8 | | .5x-11=.1(x+10) | | 3x+5-5*x+1=6x+7 | | C=D+Drt | | 6+w/5=21 | | -4x=x+15 | | 1.5=0.75a | | 0=-3x^2+-54x+-240 | | 4x+2x+5-x=10x+10 | | y=-3x^2+-54x+-240 | | 6(3x+2)=48 | | 15=2w+5 | | -7x=x+24 | | 4X+3=X+8+187 | | 2.5-.5x+3=5+2.5-5x | | -12=6x^2-22x | | -3(4y-2)-y=-4(y-5) | | 56-v=v^2 | | ln(x)=1.8 | | lnx=1.8 | | 9(x+15)=25 | | x^2=110-n | | 4x=-x-10 | | N^2=110-n | | y=-1(-1-11) | | x^2-16x-27=10 | | p(p-4)= | | 3x+15=3(2x+2) | | x+9+2x=-24 |

Equations solver categories